MODEL OF DEVELOPMENT IN THE SOUTH MUNTENIA REGION - Cristina, Partal; Andreea, Popa (Economics of Agriculture, 2012)
The sustainable development is a recent concept that appeared from the need to fight the issues of prejudicing the sustainability. This approach is very important to ensure a continuous good life style for all the generations in all the sectors and to help the consumers to be satisfied from all the productive sectors they appeal to for the daily life. This can be achieved by efforts of several parts, such as implementation and support of the regional development. The efforts that can be done in the regional level are expected to give rapid and important results in order to change and maintain the way the economy works in the way of a sustainable growing economy. This paper treats the South Muntenia region by proposing a model of regional development which refers to the development directives and the way to succeed in this area.